Comperative Performance of Agroforestry Systems in Kumharia Village of Ranchi District - Oraon, P. R.; Yadava, M. S.; Siddiqui, M. H. (Indian Journal of Agroforestry, 2020)
In Kumharia village of Ranchi district people are adopting different land use practices (such as agriculture, agroforestry, homegarden and fallow land) on their agricultural land, but they are not aware about the economic importance of different systems. In the present investigation efforts has been made to highlight the relative importance different land use systems. Amongst agroforestry systems viz. agrisilvicultural, silvipastoral and homegarden systems, wood volume production by Subabul (Leucaena leucocephala) under agrisilviculture was found maximum (422.50 cu. m ha-1), whereas in Silvipastoral system Gamhar (Gmelina arboreal produced highest wood volume (377.50 cu. m ha-1). The yield performances of agricultural, vegetable and grasses have indicated additional benefits from same land, thereby raising per unit area production in Kumharia village.